Effect of chronic alcoholism upon the parietal cells of the stomach of rats - Oliveira, C. de [UNESP]; Cruz, A. R.; Gonçalves, R. P. (My University, 1988)
The effects of chronic alcoholism upon the parietal cells of the stomach of rats were studied providing to a group of animals, only sugar cane brandy ad libitum as liquid food. A group of control animals received tap water and to both groups it was provided a balanced solid diet. During the experiment the body weight as well as liquid and solid food consumption were rated each other day. The animals were sacrificed after 45, 90 or 180 d and the effects of alcoholism evaluated at the day of sacrifice through morphological and morphometric techniques. Our results allowed us to conclude that: 1) the body weight of alcohol-treated animals increased at much slower rates when compared to controls. (2) The treated animals ingested less liquid and solid food than controls. 3) The volume of gastric secretion (ml/h/100 g of body weight) was not affected but its HCl content (mEq/l) was smaller in alcoholic rats. 4) Discrete morphological disturbance of the gastric mucosa was observed only in animals that ingested alcohol for 45 d. In the longer treatments the appearance of the mucosa was quite similar to controls. 5) The secreting mass of parietal cells decreased in alcohol treated rats. This decrease was attributed to a reduction in number of these cells.